2018
DOI: 10.1021/acs.joc.7b02986
|View full text |Cite
|
Sign up to set email alerts
|

Vinylogous Elimination/Heck Coupling/Allylation Domino Reactions: Access to 2-Substituted 2,3-Dihydrobenzofurans and Indolines

Abstract: A highly regio- and stereoselctive palladium-catalyzed domino reaction of functionalized aryl allyl ethers has been developed. Various aryl allyl ethers derived from the phosphine-catalyzed addition of electron-deficient allenes with phenol are found to be efficient substrates for the synthesis of 2-substituted 2,3-dihydrobenzofurans and indolines. It is the first example of aryl allyl ether used as an ideal and practical precursor of hard to get functionalized 1,3-butadiene for the heterocyclic compound synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Dihydrobenzofuran and indolines‐containing molecules are very important heterocyclic compounds that are found in numerous bioactive natural products and pharmaceuticals. In 2018, Yang [42] and his research group described the preparation of 2‐ substituted 2,3‐dihydrobenzofurans 58 and Indolines 61 through highly regio and stereoselective Pd catalyzed elimination/intermolecular domino Heck reaction of functionalized aryl allyl ethers 55 and halo phenols 54 as precursors (Scheme 11). Synthesis of heterocyclic frameworks from various aryl allyl ethers is difficult because of their high stabilities in metal‐catalyzed domino Heck reactions.…”
Section: Transition‐metal Catalyzed Domino‐ Cyclization For Heterocyc...mentioning
confidence: 99%
“…Dihydrobenzofuran and indolines‐containing molecules are very important heterocyclic compounds that are found in numerous bioactive natural products and pharmaceuticals. In 2018, Yang [42] and his research group described the preparation of 2‐ substituted 2,3‐dihydrobenzofurans 58 and Indolines 61 through highly regio and stereoselective Pd catalyzed elimination/intermolecular domino Heck reaction of functionalized aryl allyl ethers 55 and halo phenols 54 as precursors (Scheme 11). Synthesis of heterocyclic frameworks from various aryl allyl ethers is difficult because of their high stabilities in metal‐catalyzed domino Heck reactions.…”
Section: Transition‐metal Catalyzed Domino‐ Cyclization For Heterocyc...mentioning
confidence: 99%
“…In 2018, Yang, Wang, and co-workers reported that o-iodophenols underwent a highly regio-and stereoselective palladium-catalyzed domino reaction with functionalized aryl allyl ethers to give 2-vinyl-DHBs (Scheme 18). 66 Various aryl allyl ethers were easily prepared by the phosphine-catalyzed addition of electrondeficient allenes with phenol and were efficient substrates for the synthesis of 2-substituted DHBs.…”
Section: Scheme 17 22-difluoro-3-hydroxy-dhb From Salicylaldehydes Amentioning
confidence: 99%
“…With the aim to increase the reaction scope of the heteroannulations of 1,3-dienes and 2-iodoanilines, Wang, Yang, and co-workers reported the synthesis of 2-vinylindolines 45 using 2-iodo-N-tosylanilines and electrondeficient allyl ethers 44 as a diene surrogate (Scheme 15). 18 In particular, the use of NaHCO 3 as base promoted the vinylogous elimination of the phenoxy group on the starting allyl ether to provide the correspondent aryl diene. Subsequent intermolecular Heck coupling/intramolecular allylation afforded the substituted 1-tosyl-2-vinylindolines 45.…”
Section: Scheme 14 2-(2-ethoxyvinyl)indolines By Regioselective Hetermentioning
confidence: 99%